ENHANCING MANUSCRIPT UTILIZATION THROUGH MANUSCRIPT DIGITIZATION AND AUTOMATION: A CASE STUDY OF THE JANGKA JAYABAYA MANUSCRIPT AND KITAB ANASIR AT THE INTEGRATED LABORATORY OF ISLAMIC THOUGHT, UIN SALATIGA - Almer Samantha Hidaya; Suryanto Suryanto (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
This research aims to develop and improve the utilization of the Jangka Jayabaya Manuscript and the Anasir Book in the Islamic Thought Laboratory of UIN Salatiga through the digitization process and implementation of the Senayan Library Management System (SLiMS) Bulian automation system. The method uses Research and Development (R&D) ADDIE models with data collection through direct observation of the physical condition of the manuscript and the management process, in-depth interviews with laboratory managers, documentation studies, and comparative surveys of pre-post implementation, including quantitative analysis derived from the SLiMS Report Access feature. The results of the study show a substantial increase in utilization effectiveness: simultaneous access capacity has increased drastically (recorded to reach 17 to 32 users) in the same time session in conducting studies through scripts. In addition, accessibility has expanded to 24 hours non-stop due to the bold nature of the system, while significantly reducing the risk of physical damage to the manuscript due to direct contact. However, major obstacles include the inability of digital surrogacy to fully support in-depth codicological analysis that requires direct physical interaction with the artifact. Other challenges include limitations in technical infrastructure, especially in terms of database capacity and the resilience of the hosting domain which is still temporary.